Impact of Icebreaker in Enhanced Students' Achievement on Mathematics of The Students with Intellectual Disability - Mohammad Anwar (The Center for Disability Studies and Services Brawijaya University, 2018)
The purpose of thus research was to determine the influence of icebreaker in enhancing students achievement on mathematic of the children with mild intellectual. Disability of grade IV of SLB Putra Manunggal Gombong in the academic year of 2017 / 2018. This research used quantitative approach with the pre-experimental design using one group pre-test post-test design. The subject of this research were eight students with mild intellectual disability of grade IV of SLB Putra Manunggal Gombong in the academic year of 2017 / 2018. The technique was objective test in the form of multiple choice . the obtained data were analyzed quantitatively with Wilcoxin Sign Rank Test non parametric statistical analysis using 23 SPSS program. Based on the data analysys the post-test mean score of the research subject increased significantly, pre-test mean score was 63,12 and post-test mean score was 77,12. The result of non-parametric statistical analysis showed the score of 2 value= -2,530 with Asymp. Sig (2 tailed) = 0,011 which under 0,05 is smaller than a predetermined significance level or 0,011 < 0,05. It can be concluded that the use of icebreaker had influence in enhancing students achievement on mathematics of the children with mild intellectual disability of grade IV of SLB Putra Manunggal Gombong in the academic year of 2017/2018.